Environmental Responsibility of Enterprise in Tourism and Hotel Business in Russia - MOROZOV, Mikhail А.; MOROZOVA, Natalia S. (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018DO - 10.14505//jemt.v9.5(29).21, 2019)
The article discusses the environmental impact of tourism and hotel business on the environment and business responsibility for these negative consequences. It is shown that the ecological responsibility of the tourist and hotel business acts as a key factor determining the level of development of entrepreneurial culture in tourism and hospitality. The state of the Russian regulatory framework regulating the activities of the tourist business is analyzed. It is noted that in connection with the rapid development of hotel infrastructure in Russia, the problems of ensuring the ecological safety of hotels have become topical. It is shown that the growing number of tourists in the formation of the ecological component of tourism is the emergence of a new category of tourists who, in the process of traveling, pay special attention to the issues of ecology, preservation of the environment, development of the planet. It is emphasized that the ecological condition of the tourist destination is an important aspect of the travel motivation. The directions of increasing the environmental responsibility of entrepreneurship in tourism and hospitality are proposed, as well as the formation of an ecologically responsible tourist.